The Ongoing Quest for Culturally-Responsive Assessment for Indigenous Students in the U.S. - Trumbull, Elise; Nelson-Barber, Sharon (Frontiers in Education, 2019)
Efforts in the U.S. to design curriculum, instruction, and assessment based on Indigenous systems of knowledge and ways of teaching and assessing learning have been mounted wherever Indigenous peoples live. Yet, Western-style education in those places often continues to dominate, to the detriment of Indigenous students' engagement and school completion. Assessment, in particular, has long aroused great concern because many common assessments are not only ineffective but also destructive for Indigenous students—especially when they are used to make high-stakes decisions that affect students' life outcomes. Among such decisions are eligibility for passage from one grade to the next, high school graduation, and college admission. Much is known about how to make assessment culturally-responsive for Indigenous students, but it is often the case that successful programs and practices are jettisoned when new country-wide or state-wide policies are instituted. In the U.S., the most egregious recent case of public policy's interfering with highly successful education of American Indian and Alaska Native students was the No Child Left Behind Act of 2000. Driven by demands to attain high performance on standardized tests, teachers truncated or abandoned strong culture-based instruction in favor of instruction thought to prepare students to do well on the tests. This is just one example of how decision makers under external pressures tend to revert to “best practices” or “the One Best Way,” evoking historical movements to extinguish Indigenous languages and cultures. This article discusses obstacles to culturally-responsive assessment for Indigenous students, describes examples of efforts in the U.S. and elsewhere to improve assessment for Indigenous students, explores the concept of “culturally-valid assessment,” and interleaves recommendations for going forward constructively within various sections of the paper.